Inklusi Keuangan dan Literasi Keuangan Syariah di Era Digital: Analisis Dampaknya terhadap Pertumbuhan Ekonomi - M. Wanri Wahyudin; Mastur Mastur; Vivi Ulfatul Aziz; Sutia Arini; Rima Devi Yani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The development of digital technology has driven transformation in the financial system, including within the Islamic finance sector. In this context, Islamic financial literacy and financial inclusion are important factors that can enhance public participation in the formal financial system and support economic growth. However, the levels of Islamic financial literacy and financial inclusion among the public remain relatively low, which may hinder the optimal contribution of Islamic finance to the economy. This study aims to analyze the impact of Islamic financial literacy and financial inclusion on economic growth in the digital era. The research employs a quantitative approach using multiple linear regression analysis with the assistance of SPSS software. The data were collected through questionnaires distributed to respondents who met the research criteria. The results show that Islamic financial literacy has a positive and significant effect on economic growth, indicating that increased public understanding of Islamic financial concepts and products can encourage more productive economic activities. Furthermore, financial inclusion also has a positive and significant effect on economic growth, suggesting that broader access to formal financial services contributes to increased economic activity. The findings of this study indicate that improving Islamic financial literacy and expanding access to financial services, particularly through digital financial technology, can serve as an important strategy in promoting more inclusive and sustainable economic growth.